A Longitudinal Study of Head Circumference Trajectories in Autism and Autistic Traits. - Ashley, Sarah A.; Merritt, Kate; Solmi, Francesca; Laguna, Pedro L.; Reichenberg, Abraham; David, Anthony S. (Journal of Autism & Developmental Disorders, 2026)
Increased head circumference is an established finding in autism spectrum disorder (ASD); however, it is unclear when this increase occurs, if it persists and whether it manifests across the whole ASD spectrum. Head circumference is a strong predictor of brain size and can therefore provide key insights into brain development in ASD. We used data from the Avon Longitudinal Study of Parents and Children to compare head circumference trajectories from birth to 15 years in children with an ASD diagnosis (N = 78, controls = 6,404) or elevated autistic traits as measured using the Social Communication Disorder Checklist (N = 639, controls = 6,230). Exploratory analyses were conducted in those with ASD and co-morbid cognitive learning needs (CLN). Children with an ASD diagnosis had larger head circumference from birth across childhood and adolescence compared to controls in univariable (B = 0.69, 95% confidence interval [CI]: 0.28–1.09, p = 0.001) and multivariable models (B = 0.38, 95% CI: 0.003–0.75, p = 0.048). Differences were more marked in those with co-morbid CLN. Children with elevated autistic traits had significantly smaller head circumference compared to controls. There was weak evidence of group differences when height was included as a covariate. Head circumference trajectories in ASD deviate from control children and persist until adolescence. Autistic traits were associated with smaller head circumference, suggesting distinct growth trajectories between clinical cases from those with non-clinical traits.